ANTIBACTERIAL ACTIVITY OF METHANOL EXTRACT FROM INGGILI FRUIT (Xylocarpus granatum) AGAINST Propionibacterium acnes AND Escherichia coli USING WELL DIFFUSION METHOD - Wahyu Isnaini Nurhidayanti; Achmad Kadri Ansyori; Reksi Sundu (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2023)
Inggili is a type of mangrove plant that has been traditionally used by the community for medicine. It contains many active compounds that function as antibacterials. Based on empirical data, inggili fruit is used to remove acne on the skin and diarrheal diseases. This study aims to determine the antibacterial activity of methanol extract of inggili pulp in inhibiting Propionibacterium acnes and Escherichia coli bacteria using the sumuran diffusion method. The research conducted is experimental. The object under study was the antibacterial activity of inggili fruit extract against Propionibacterium acnes and Escherichia coli bacteria. Antibacterial activity was tested using the sumuran diffusion method with extract concentrations of 10%, 15%, and 20%. The negative control used was 1% DMSO and the positive control used was 0.1% chloramphenicol